Post-colonial diasporic condition and its effects on the aesthetics of Filipino-American contemporary visual arts c. 1980 to 2005 in California - Ramirez, Veronica Esposo (2007)
The Filipino-American visual artists migrate voluntarily (as migrants) or consequentially (as migrant workers, students, etc.) to join their colonizers in their homeland. In this new world, the artist-diasporas mingle with white and multi-ethnic people. They make art that represents their identity, social history and post-colonial diasporic concerns, not only to express themselves but also to penetrate the art world. This art world is one occupied by a variety of stakeholders: white Americans as well as "people of color," public and private museums, private galleries, curators, patrons, collectors, likewise fellow Filipinos. In the process of socialization, there are elements that the artists absorbs as well as shed off. In making art, they may produce art that is neither Filipino nor American but a hybrid of culture and influences surrounding them. How Filipino-American social history and post-colonial diasporic concerns affect art-making, and the formation of a Filipino-American visual art world are the interest of this study. The aim of this study is to analyze the formation of Filipino-American visual art in America, particularly the social history and the effects of post-colonial diasporic concerns on Filipino-American visual art. Specifically, it aimed to answer the following research questions: 1. What are the effects of post-colonial diasporic concerns of Filipino-American visual artists on the social history of the Filipino-American visual art? 2. How can the aesthetics of the Filipino-American visual art be described? 3. What distinct characteristics of Filipino-American visual art have emerged as a result of the social conditions affecting it? Six out of 11 Filipino-American visual artists who practice art-making in California were chosen for this study: Jose Morales, Manuel Ocampo, Eliseo Art Silva, Stephanie Syjuco, Mel Vera Cruz and Carlos Villa. The artists were visited in their homes and art studios in California in September 2005. Those who were not available for interview were communicated with through electronic means and telephone. The primary research instrument used was interview questions. Observation, documentation, analysis of artworks and documents were done to supplement the data gathered from the research instrument. Findings; Based on the analyses of the data, the major findings of this study are as follows: 1. Although social benefits, rights and privileges have been mediated for them by their predecessors, the Filipino-American visual artists are not free from concerns relating to an artworld that is pluralistic and multicultural. 2. In their desire to penetrate the artworld in America, they are confronted with cultural issues of identity, cross-cultural interaction, acculturation; political racial issues and economic difficulties and social conditions - concerns that are inherent to their status as a post-colonial diaspora. 3. Filipino-American visual artists certainly search for their identity but not for the reason of reconstructing the culture that they once lived in their homeland. They feel the need to distinguish themselves from the multicultural composition of their new world. 4. The identity of the Filipino-American visual art is neither identical to the Filipino nor to American but a hybrid of a new kind of art as a result of the mixture of two (or even more) cultures in one form. 5. By joining the American colonizers in their homeland, the Filipino-American visual artists clearly exercise colonial patronage. Nevertheless, they exercise counter colonial discourse through the statements they make in their artworks. 6. Filipino-American visual artists contribute to cultural development in their own ways and through the body of works they produce. Conclusions; In the light of the findings of this study, the conclusions are as follows: 1. The post-colonial diasporic concerns that affect Filipino-American visual art pertain to identity, cultural integration, cross-cultural interactions, acculturation, racial issues and economic difficulties and social conditions. The search for identity means three things to the Filipino-American visual artists: identity as an artist, as a Filipino and as a Filipino-American artist. Bonding among the artists themselves is strong but when they integrate into the rest of the Filipino-American community, they are met with ambivalent feelings of acceptance and support. Given certain qualities and characteristics, they are able to interact with ease among "artists of color" and white Americans. Acculturation is manifested more in their living standards, use of time, style of clothing and other personal effects. In art, they are acculturated to the variety of ways and possibilities of art-making available in a developed country. Penetrating the art market was no easy task for the Filipino-American visual artists, who experienced racial discrimination and marginality. These experiences are manifested in their artworks. Economically, it is not only the art organizations that suffer from difficulties and state spending priorities. The artists themselves have to battle with the demands of survival in a First World Country not only to live and produce art but to sustain their family. 2. The social history of the Filipino-American visual artists is characterized by three factors: (a)aesthetics (influences, patronage, material, and themes) (b)influences and (c)patronage. Their aesthetics is formed by content that expresses Filipino culture and their personal identity; and form that has been shaped and influenced by multicultural orientation and contemporary techniques of art production. A strong patronage across cultures of Filipino-American visual art is seen through exhibitions, fellowship, grants and awards. 3. It is evident that the identity of the Filipino-American visual art is neither identical to the Filipino nor to American but a hybrid of a new kind of art as a result of the mixture of two (or even more) cultures in one form. Although they make art in styles that originated from the West, such as abstract expressionism, social realism, and installation, they still express something Filipino in choice of subject matter, colors, symbols or form.